FRACTAL APPROACH IN MODELLING OF EARTHQUAKES - Silberschmidt V.V. (My University, 1996)
A model for an earthquake simulation is proposed with the use of a fractal approach. Multiple generation and coalescence of shear faults in stochastic brittle media (modelled as a 2d lattice) are considered to be a source of seismicity. Dynamics of local failure events are governed by accumulation of shear defects, described in terms of continuum damage mechanics. Fractal tree structure is used as an analogue for a stress redistribution process. Energy release, caused by the non-uniform failure, is studied for a non-conservative case. Effect of various types of rocks' properties stochasticity on energy release dynamics is analysed with a utilization of multifractal formalism. The latter is shown to be an additional method for seismicity characterization.